Gastrointestinal Histoplasmosis Presenting as an Acute Abdomen with Jejunal Perforation - Bryan R. Anderson; Jaron Marriott; Chinthaka Bulathsinghala; Humayun Anjum; Salim Surani (Case Reports in Medicine)
Introduction. Gastrointestinal histoplasmosis (GH) is a well-described albeit uncommon disease. It is found almost exclusively in the immunocompromised host, especially those with untreated HIV and low CD4 counts. Presentation with intestinal perforation is seen mostly commonly in the colon. We present a patient with jejunal perforation, and there have been only 3 previous cases reported in the literature. Case. A 39-year-old male with known, untreated HIV presented to the ED with an acute abdomen after experiencing worsening intermittent abdominal pain for 2 months before that was associated with nausea, vomiting, diarrhea, and weight loss. CT of the abdomen and pelvis revealed evidence of gas in the mesentery, small bowel thickening, edema, and free fluid in the abdomen. Emergency exploratory laparotomy was conducted. Intraoperative findings included a perforated jejunum that was studded with nodular lesions as well as mesenteric masses. Histopathologic exam of these mesenteric masses and jejunal lesions were positive for histoplasmosis. Conclusion. Disseminated histoplasmosis is a life-threatening disease that occurs nearly exclusively in immunocompromised hosts. Untreated, mortality is as high as 80%. This rare presentation with jejunal perforation highlights the need for awareness of histoplasmosis involvement throughout the entirety of the GI tract.